Group A streptococcal infection in the United Kingdom: an emerging threat - Kamran Zaman; Abdelmonem Siddiq; Aroop Mohanty; Darwin A. León-Figueroa; Joshuan J. Barboza; Tareq AL-Ahdal; Ranjit Sah (Exploration of Medicine, 2023)
Within group A Streptococcus (GAS), only Streptococcus pyogenes exhibits clinical significance. GAS is typed serologically based on unique surface proteins and critical virulence factors, such as a hyaluronic acid capsule that shields GAS from phagocytosis. The burden of GAS was estimated in the last five years as 14,000 to 25,000 cases of the invasive group A streptococcal disease in the USA with an estimated death from 1,500 to 2,300 cases per year. Early in the summer of 2022 in England, there was more scarlet fever than was anticipated. Early in the current season, the number of notifications rose to unusual heights. The analysis of invasive GAS (iGAS) isolate typing data shows that this season has seen a wide variety of encoding mature M protein (emm) gene sequence types found. Therefore, public health authorities should think about initiatives to increase clinicians’ and the general public’s awareness of GAS infections and to promote their quick diagnosis, molecular testing and antibiotic susceptibility testing, and standard treatment.